Efficacy and safety of ultrasound-guided serratus anterior plane block for postoperative analgesia in thoracic surgery and breast surgery: A systematic review and meta-analysis of randomized controlled studies - Liang, Weidong; Zhang, Wenfu; Wu, Yingting; Liu, Rongrong; Qiu, Zhengang; Zhong, Ruipeng; Lan, Qinghai; Wang, Yufei; Liu, Jinlong; Zhong, Maolin; Hu, Shuhui (Frontiers in Anesthesiology, 2022)
Objective Serratus anterior plane block (SAPB) is a new perioperative analgesia for patients undergoing thoracic and breast surgery. The primary purpose of this systematic review and meta-analysis was to investigate whether ultrasound-guided SAPB combined with general anesthesia provides safer and more effective postoperative analgesia than general anesthesia alone or general anesthesia combined with incisional local infiltration anesthesia in patients receiving thoracic and breast surgery. Methods We systematically searched PubMed, Embase, Web of Science and the Cochrane Library databases for clinical randomized controlled trials (RCTs) of SAPB for postoperative analgesia in thoracic and breast surgery. The primary outcome was the postoperative pain score. Secondary outcomes included intraoperative opioid consumption, 24-h postoperative opioid consumption, time to first use of analgesics, number of patients requiring urgent additional analgesics, opioid complications (postoperative nausea, vomiting, respiratory depression, constipation, dizziness, sedation) and length of hospital stay. The risk of bias was assessed using the Cochrane method and Jadad score. Results A total of 29 RCTs with 1,978 patients were included. Twelve studies included thoracic surgery, and 17 studies included breast surgery. The results of the meta-analysis showed that the rest or movement pain scores of the SAPB group were significantly lower than those of the control group at each postoperative time point. In addition, morphine consumption was significantly reduced in the SAPB group at 24 h postoperatively (standardized mean differences [SMD], −2.77; 95% confidence interval [CI], −3.56 to −1.97; P < 0.01). Intraoperative opioid consumption was significantly reduced in the SAPB group (SMD, −0.66; 95% CI, −1.03 to −0.28; P < 0.01); and the number of patients requiring urgent additional pain medication postoperatively (risk ratio [RR], 0.34; 95% CI, 0.27 to 0.42; P < 0.01) was significantly lower; and the time to first use of analgesics was significantly longer (SMD, 3.49; 95% CI, 2.23 to 4.74; P < 0.01); and the incidence of postoperative nausea and vomiting (PONV) (RR, 0.43; 95% CI, 0.34 to 0.54; P < 0.01), constipation (RR, 0.12; 95% CI, 0.03 to 0.52; P < 0.01; I2 = 0), dizziness (RR, 0.24; 95% CI, 0.06 to 0.92; P < 0.05; I2 = 0) and sedation (RR, 0.07; 95% CI, 0.01 to 0.52; P < 0.01; I2 = 0) were significantly lower; the length of hospital stay was significantly shorter (SMD, −0.28; 95% CI, −0.46 to −0.09; P < 0.01) and the SAPB group have a significantly reduced the incidence of postoperative pain syndrome at 3 months. Conclusions Compared with no SAPB block, ultrasound-guided SAPB provides superior postoperative analgesia by reducing postoperative pain scores, the incidence of postoperative pain syndrome at 3 months and perioperative opioid consumption in patients after thoracic and breast surgery. At the same time, SAPB reduces the incidence of side effects of opioids and shortens the length of hospital stay. SAPB can be used as a feasible technique for multimodal analgesia in the perioperative period.